Drugs in the COVID-19 pandemic: Analysis of the commercialization of azithromycin, hydroxychloroquine, ivermectin and nitazoxanide in Brazil (Research, Society and Development, 2022)
The coronavirus infection (COVID-19) has affected more than 22 million Brazilians, causing more than 600,000 deaths Until the vaccines were available, there was an intense search in Brazil for promising candidate drugs for the treatment of the disease, including antibiotics, antimalarials, antiparasitics and immunosuppressive agents. Despite intense investigations, there are still no safe and effective drugs based on scientific evidence against this virus. The objective of this study was to evaluate the impact of the marketing of drugs azithromycin, hydroxychloroquine, ivermectin and nitazoxanide in Brazil during the COVID-19 pandemic period of 2020. Data on the marketing of drugs were taken from the National Controlled Products Management System (SNGPC). The results showed that among the drugs investigated, azithromycin was the most marketed in the country, followed by hydroxychloroquine, ivermectin and nitazoxanide. The Brazilian region with the highest consumption of these drugs was the Southeast, followed by the South, Northeast, Midwest and North. From the information analyzed in the study, we concluded that there was a potential consumption in Brazil of the investigated drugs, especially azithromycin. These data serve as a warning for the elaboration of future public strategies that adequately educate the population and health professionals about the risks of using drugs without safety and proven efficacy against COVID-19.